John of the Cross (Routledge (Firm))
1 online resource
Keywords: "This book explores the life and teaching of John of the Cross, the Spanish mystic who remains a major source of Western thought on spirituality, theology and mysticism. Leading academics discuss the importance and legacy of John from historical, theological, philosophical, pastoral, ecumenical, psychological and literary perspectives. In particular the book focuses on his place in Carmel, his understanding of desire, and the role of transformation in his theology. Approaching John in the context of the late medieval mystical tradition, it offers a timely re-evaluation of his work and a significant re-assessment of his relevance in the context of current debates"--